An Empirical Study of H-share IPO Underpricing - Qiu, Liting (2009)
Since Tsingtao Brewery firstly listed in Hong Kong Stock Exchange in 1992, H-share IPOs experienced a boom in recent years. Since listing in Hong Kong stock market is a major means for Chinese government to privatize state-owned enterprises (SOEs), it is worth to study the determinants of H-share underpricing. Generally, there are four potential explanations, namely asymmetric information hypothesis, institutional explanations, ownership and control hypothesis and behavioral explanations. In this study I am interested about the effect of IPO subscription rate which relates to adverse selection hypothesis and the explanatory power of ex ante uncertainty hypothesis and signaling hypothesis. More importantly, I include the state retention rate as a proxy for ownership and control hypothesis since H-share companies have high state ownership. The result shows that the subscription rate is significantly and positively related to the level of underpricing, supporting the adverse selection theory but ex ante uncertainty and signaling hypothesis do not work well in H-share market. Contrary to my prediction, the state retention rate has weak impact on the excess initial return.